Metaphor and Cultural Narratives of the Economy: Analyzing Symbolic Value under the Context of the 2008 Financial Crisis and Its Aftermath - Valdivia, Pablo (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2023)
This article has two interconnected goals: 1) to provide an updated view regarding metaphor and social neuroscience concerning analogical cognition/modeling; 2) to analyze how metaphoricity activates hegemonic cultural narratives of the economy under the context of the 2008 Financial Crisis and its aftermath in a sample of Spanish press outlets and, via symbolic value cross-comparison analysis, in Todo lo que era sólido (2013) by Antonio Muñoz Molina and in En la orilla (2013) by Rafael Chirbes. Both texts offer transposable conditions for scalability.